Indigenous reconciliation - Irarrázaval, Diego (2000)
The continent hides its truths. Hardly anyone accepts being Indian-Afro-Mestizo-American. Each person can tell their story. In my case, I have been poorly educated in a Chilean society corroded by racism, which hides what is mestizo and indigenous; I found the outside fascinating and our interiority of little value. It's been hard for me to change. Contact with indigenous peoples in Peru has opened my eyes. Now I aspire to collaborate on the path of reconciliation. It seems very important to me what was previously accidental. I am convinced that if the indigenous/mestizo origins are accepted, then we will have a good future in our continent.